Impact of Digital Marketing on the Growth of Business in Nepal - Thapa, Brikshya; Bista, Nar Bahadur (Nepalese Journal of Management, 2025)
This study examines the impact of digital marketing on the growth of business in Nepal. Growth of business is the dependent variable. The selected independent variables are digital marketing channels, content quality and relevance, marketing strategies, technological infrastructure, and budget allocation. The primary source of data is used to assess the opinions of respondents regarding digital marketing channels, content quality and relevance, marketing strategies, technological infrastructure, budget allocation, and growth of business. The study is based on primary data of 128 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of digital marketing in the growth of business in Nepal. The study showed a positive impact of digital marketing channels on growth of business. It indicates that digital marketing is a primary driver of business growth in today’s competitive landscape. Similarly, the study showed a positive impact of content quality and relevance on growth of business. It indicates that creating highly relevant content is crucial for effective business growth. Likewise, the study also revealed a positive impact of marketing strategies on growth of business. It indicates that long-term plan for achieving a company’s goals lead to growth of business. Further, the study observed a positive impact of technological infrastructure on growth of business. It indicates that implementing automation or AI-driven solutions within digital marketing processes drives growth of business. In addition, the study observed a positive impact of budget allocation on growth of business. It indicates that allocating a sufficient budget for digital marketing leads to growth in business.